Declining Muslim Religious Levels in the Middle East and North Africa Region - Tasya Rachmadila Ramadhani; Anshori, Isa (Universitas Nahdlatul Ulama Surabaya, 2022)
At present it seems that the religiousness of Muslims is decreasing more and more. This can be seen from the increasing number of Muslims with liberal views and also by the increasing number of atheism, especially in the Middle East and North Africa. The causes and how the decline in the quality of reverberation, especially in areas where the majority are Muslim, will be discussed in this article. This research will use the literature study method by looking for various sources of available statistical data and surveys. Even though the countries in the region are Islamic countries, the research results show that even though the number of Muslim populations is increasing every year, the religiousness of the people in the region has decreased dramatically, especially after the end of the Arab Spring in 2011. Di masa sekarang tampaknya kereligiusan umat muslim semakin lama semakin menurun. Hal ini dapat terlihat dari semakin banyaknya umat muslim yang berpandangan liberal dan juga dengan meningkatnya jumlah ateisme khususnya di kawasan timur tengah dan afrika utara. Penyebab dan bagaimana turunnya kualitas bergama khususnya di kawasan yang mayoritas beragama islam tersebut akan menjadi pembahasan dalam artikel ini. Penelitian ini akan menggunakan metode studi literatur dengan mencari berbagai sumber data statistik dan survei yang telah tersedia. Walaupun negara-negara di kawasan tersebut adalah negara islam, hasil penelitian menunjukkan bahwa meskipun jumlah populasi umat muslim setiap tahunnya semakin bertambah banyak, tetapi kereligiusan masyarakat di kawasan tersebut semakin menurun secara dramatis terutama setelah berakhirnya arab spring pada tahun 2011.